The Highly Efficient Synthesis of 1,2-Disubstituted Benzimidazoles Using Microwave Irradiation - Monica Nardi; Sonia Bonacci; Natividad Herrera Cano; Manuela Oliverio; Antonio Procopio (Molecules, 2022)
The benzimidazole ring of the heterocyclic pharmacophores is one of the most widespread and studied systems in nature. The benzimidazole derivative synthesis study is a crucial point for the development of a clinically available benzimidazole-based drug. Here, we report a simple microwave assisted method for the synthesis of 1,2-disubstituted benzimidazoles. The combination of the molar ratio of N-phenyl-o-phenylenediamine:benzaldehyde (1:1) using microwave irradiation and only 1% mol of Er(OTf)3 provides an efficient and environmental mild access to a diversity of benzimidazoles under solvent-free conditions. The proposed method allows for the obtainment of the desired products in a short time and with very high selectivity.